Both feature comparisons and location comparisons are subject to bias - Humphries, Ailsa; Chen, Zhe; Cave, Kyle R. (Attention, perception & psychophysics, 2021)
Four experiments explore the generalizability of two different types of bias in visual comparison. The first type is a spatial congruency bias, in which two target stimuli are more likely to be classified as matching (‘same’) if they appear successively at the same location. The second type is an analytic bias, which varies depending on the overall similarity of the displays and the need to select specific parts from each object. Both types of bias had previously been demonstrated in comparisons based on shape and other visual features. The current tasks move beyond feature comparisons, requiring the comparison of the local positions of visual elements (dots or letters) that appear within each pattern. Given the privileged role of location in visual representations and attentional selection, it is important to test how visual comparisons of location differ from comparisons of shape and other features. The spatial congruency bias is replicated in the comparison of local positions and, as in previous experiments, its strength diminishes when the displays being compared are less similar to one another. Also, as demonstrated previously with letter comparisons, there is an analytic bias shifting responses toward ‘different’ when the displays being compared are less similar to one another. Responses are also shifted more toward ‘same’ in location comparisons relative to feature comparisons. The general pattern of results suggests that as more attentional selection is required in a comparison task, there is a stronger overall bias to respond ‘different’.